Isolation, Molecular Characterization, and Mapping of Four Rose MLO Orthologs - Kaufmann, Helgard; Qiu, Xianqin; Wehmeyer, Juliane; Debener, Thomas (Frontiers in Plant Science, 2012)
Powdery mildew is a major disease of economic importance in cut and pot roses. As an alternative to conventional resistance breeding strategies utilising single-dominant genes or QTLs, mildew resistance locus o (MLO)-based resistance might offer some advantages. In dicots such as Arabidopsis, pea and tomato, loss-of-function mutations in MLO genes confer high levels of broad-spectrum resistance. Here, we report the isolation and characterisation of four MLO homologues from a large rose EST collection isolated from leaves. These genes are phylogenetically closely related to other dicot MLO genes that are involved in plant powdery mildew interactions. Therefore, they are candidates for MLO genes involved in rose powdery mildew interactions. Two of the four isolated genes contain all of the sequence signatures considered to be diagnostic for MLO genes. We mapped all four genes to three linkage groups and conducted the first analysis of alternative alleles. This information is discussed in regards to a reverse genetics approach aimed at the selection of rose plants that are homozygous for loss of function in one or more MLO genes.